A high-sensitivity hydrogen gas sensor based on Ag nanoparticle-decorated porous Co3O4 nanorods - Sinh, Vu Hung; Quang, Duong Tuan; Phuong, Tran Quy; Hoa, Tran Thai; Hieu, Nguyen Van; Cuong, Nguyen Duc (Vietnam Journal of Science and Technology, 2024)
In this report, Ag nanoparticle-decorated cobalt carbonate hydroxide microflowers were synthesized using a simple hydrothermal approach without using surfactants, which were used as precursors to prepare Ag nanoparticle-decorated porous Co3O4 nanorods through an annealing process. The porous Co3O4 nanorods were composed of small primary nanoparticles with a size of ~ 10 nm, and their surface was decorated with uniform Ag nanoparticles (~ 10 nm). Sensors based on the porous Co3O4 nanorods decorated with Ag nanoparticles have higher sensitivity and selectivity to H2 gas than other reduced gases, as well as rapid response-recovery times. The enhanced H2 sensing properties of the sample may be attributed to the excellent catalytic features of Ag nanoparticles and unique porous Co3O4 nanorods. The results demonstrated the potential of Ag nanoparticle-decorated porous Co3O4 nanorods as sensing materials for the detection of hydrogen gas at low temperatures.